2020
DOI: 10.1186/s11689-020-09320-7
|View full text |Cite
|
Sign up to set email alerts
|

Expressive language development in adolescents with Down syndrome and fragile X syndrome: change over time and the role of family-related factors

Abstract: Background: It is well known that individuals with Down syndrome (DS) or fragile X syndrome (FXS) demonstrate expressive language difficulties beginning early in childhood. It is less clear, however, whether expressive language skills change during the adolescent period in these individuals, and if any of these changes are syndrome specific. Studying this, as well as the role of maternal and family-related factors in expressive language development, may provide the foundation for efficacious interventions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 105 publications
1
7
0
Order By: Relevance
“…In most cases FXS is driven by a tri-nucleotide repeat expansion in the 5 0 UTR of the fragile X messenger ribonucleoprotein 1 (FMR1) gene, which leads to epigenetic silencing and complete loss of the encoded RNA binding protein FMRP (Bagni et al, 2012;Darnell et al, 2011;Dictenberg et al, 2008). While both DS and FXS are characterized by broad phenotypic variability, patients with DS and FXS share intellectual disability and deficits in expressive communication, as well as increased rates of autism, seizure disorders, and mental health disorders compared with the general population (Capone et al, 2006;Del Hoyo Soriano et al, 2020;Finestack et al, 2009;Jensen and Bulova, 2014;Martin et al, 2009;Tranfaglia, 2012). Other phenotypes diverge; unlike patients with FXS, patients with DS are at increased risk for childhood leukemias and DS is one of the most common genetic causes of early-onset Alzheimer's disease (Mateos et al, 2015;Tcw and Goate, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases FXS is driven by a tri-nucleotide repeat expansion in the 5 0 UTR of the fragile X messenger ribonucleoprotein 1 (FMR1) gene, which leads to epigenetic silencing and complete loss of the encoded RNA binding protein FMRP (Bagni et al, 2012;Darnell et al, 2011;Dictenberg et al, 2008). While both DS and FXS are characterized by broad phenotypic variability, patients with DS and FXS share intellectual disability and deficits in expressive communication, as well as increased rates of autism, seizure disorders, and mental health disorders compared with the general population (Capone et al, 2006;Del Hoyo Soriano et al, 2020;Finestack et al, 2009;Jensen and Bulova, 2014;Martin et al, 2009;Tranfaglia, 2012). Other phenotypes diverge; unlike patients with FXS, patients with DS are at increased risk for childhood leukemias and DS is one of the most common genetic causes of early-onset Alzheimer's disease (Mateos et al, 2015;Tcw and Goate, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(19,20). In addition, the ELS-N procedures can distinguish between language profiles on specific neurodevelopmental populations (21) and capture change over time (22). For all these reasons, the ELS-N task has been proposed as a potential outcome measure for clinical trials involving individuals with intellectual and developmental disabilities (23)(24)(25) and has been used in several clinical trials for these populations (e.g., Protocol Neu-2566-FXS-001; A Safety Study of NNZ-2566 in Patients With Fragile X Syndrome, 2013-2017).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, when compared either to individuals with typical development (TD) or with other neurodevelopmental disabilities (NDDs) of similar mental ages (MAs), individuals with DS demonstrate, as a group, relative strengths in the areas of nonverbal communication, gross motor skills, visual motor integration, and visual imitation 4,5 . In contrast, auditory short-term memory, episodic memory, aspects of visuospatial construction and executive function, and language are areas that are particularly challenging for individuals with DS [6][7][8][9][10][11][12] .Language skills constitute one of the most impaired aspects of the cognitive profile of individuals with DS. Research has also shown, however, that within the area of language some aspects are generally more affected than others among those with DS 9 .…”
mentioning
confidence: 99%
“…Indeed, there is considerable research documenting that multiple areas of expressive language lag behind MA expectations [13][14][15] . For example, individuals with DS score less well on measures of vocabulary and syntax when compared to younger TD peers 10,[16][17][18][19] and similarlyaged peers with other developmental disabilities, both matched on MA 17,20,21 . There is also evidence suggesting that expressive syntax skills are more impaired than are expressive vocabulary skills in individuals with DS 22 as expressive syntax appears to lag relative to both nonverbal cognition and vocabulary level-expectations [13][14][15]23,24 .…”
mentioning
confidence: 99%
See 1 more Smart Citation